A new auxetic structure with enhanced stiffness via stiffened elliptical perforations. (30th December 2020) - Jafari Nedoushan, Reza; Yu, Woong-Ryeol
Abstract: Auxetic materials, a class of metamaterials with negative Poisson's ratio, have been extensively studied due to their attractive mechanical properties. In this study, an auxetic material was developed using new perforation shapes with stiffeners. Standard elliptical perforations were stiffened and analyzed by the finite-element method. Periodic boundary conditions were applied to the unit cell of the new shapes and their effective Poisson's ratio and Young's modulus were calculated. The finite-element analysis found that the proposed stiffened perforated sheets exhibited auxetic behavior and had enhanced stiffness compared with standard elliptically perforated sheets.